The commercial potential of forest trees as medicinal and health ingredients - Syamsul Hidayat; Ervizal A.M. Zuhud; Didik Widyatmoko; Bahruni BAHRUNI; Irmanida Batubara (Society for Indonesian Biodiversity, 2021)
Abstract. Hidayat S, Zuhud EAM, Widyatmoko D, Bahruni, Batubara I. 2021. The commercial potential of forest trees as medicinal and health ingredients. Biodiversitas 22: 2795-2804. Indonesian forests contain many trees that belong to medicinal plants classified as non-timber forest products (NTFP). Although these plants have been used from generation to generation by several ethnic groups and even some of them have become commercial goods, many species have not received special attention in terms of their cultivation. This study aimed to explore the commercial value of forest trees as medicinal ingredients and obtain a recommended ranking for their cultivation. The method used was market surveys to herbal stores and questionnaires to experts related to medicinal plants. The results showed that there are 59 species of forest trees used as medicinal ingredients and health supplements. Cinnamomum burmanni, Morinda citrifolia, and Moringa oleifera have the most diverse commercial products in drugs and health stores. These three species also have active ingredients that potentially substitute for chemical drugs. Following the advice of medicinal plant experts, these three species are also included in the ten species recommended for immediate cultivation.